Effect of supplementation of amino acid chelate of Zn, Cu, Mn and Co heptagluconate on performance of Barbari goat kids - CHAUDHARY, U B; TRIPATHI, M K; TRIPATHI, PRABHAT; DUTTA, T K; GUPTA, BHAVNA; SIROHI, H V (The Indian Journal of Animal Sciences, 2016)
Male Barbari kids (56), 7 to 8 months of age and weighing19.2± 2.9 kg were randomly divided into 4 equal groups to assess the effect of source (inorganic or organic) and level of Zn, Cu, Co and Mn on intake and growth performance. The kids of control group were fed inorganic source of Zn, Cu, Co and Mn while other groups were fed organic complex (Zn, Cu and Mn amino acid and Co as cobalt heptagluconate at 50, 75 and 100 % of inorganic requirement. Feeding cum growth experiment lasted for 105 days. The live weight of kids at initiation of experiment varied from 19.12 to 19.67 kg, and final live weight ranged between 23.4 to 25.01 kg among the four groups. Total gain and average daily gain varied from 4.82 to 5.34 kg and 45.9 to 50.9 g respectively, which were not different among the four groups. The feed intake varied from 3.9 to 4.0 % of live weight. Live weight change remained lower in kids supplemented 75 and 100% organic trace minerals and had a pooled 6.9 and 9.8% lower average daily gain respectively. The feed efficiency and feed conversion ratio was similar among the four groups. Supplementation of 50% organic minerals provided daily gain equal to inorganic supplemented kids, while 75 and 100 % organic supplementation deteriorated daily gain. Therefore, at 50% organic supplementation levels, the bio-availability of Zn, Cu, Co and Mn have met the daily requirement of kids in relation to recommended requirements of inorganic minerals.